STRATEGI KOMUNIKASI KOMUNITAS KAMPUNG LALI GADGET WONOAYU DALAM MENGURANGI KECANDUAN GADGET PADA ANAK - Tabi’ina Alfi Rohmah (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the communication strategies implemented by the Kampung Lali Gadget Community in Wonoayu to reduce the level of gadget addiction among children. Using a qualitative research method with a descriptive approach, the study explores the communication processes, types of activities, and behavioral changes observed in children after participating in the community’s programs. The findings indicate that Kampung Lali Gadget applies direct interaction–based communication strategies through two main approaches. First, the community introduces traditional games played collaboratively to rebuild social relationships, increase physical activity, and create enjoyable play experiences without dependence on digital devices. Second, the community introduces local food culture through rice-planting activities as a form of education rooted in nature, local culture, and understanding of food production processes. These strategies have proven effective in providing positive stimulation that encourages children to become more focused, more diligent, and significantly reduce their gadget use. The results of this study demonstrate that communication strategies integrating local wisdom, outdoor activities, and social interaction can serve as an effective approach to addressing gadget addiction among children in the digital age. This research is expected to serve as a reference for other communities in developing relevant and sustainable programs